PENGARUH HARGA, KUALITAS PRODUK, DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BRAND H&M - Putri, Agnesh Kurnia Pratama; Suratno, Ignatius Bondan (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
The purpose of this study was to determine: (1) the effect of prices on consumer HM brand purchasing decisions; (2) the effect of product quality on consumer purchasing decisions for HM brand; (3) the effect of product design on HM brand consumer purchasing decisions. This research is quantitative research. The collected data were primary data which were collected by questionnaires. The data were taken from 100 samples, selected by accidental sampling technique. The data were analyzed by Chi-Square test. The results showed that: (1) there was no positive and significant effect of price on purchasing decisions with a Chi-Square value 2.532 and Asymp. Sig. value (2-sided) 0.112; (2) there was a positive and significant influence of product quality on purchasing decisions with a Chi-Square value 31,014 and Asymp. Sig. value (2-sided) 0.000; and (3) there was a positive and significant influence of product design on purchasing decisions with a Chi-Square value 63.846 and Asymp. Sig. value (2-sided) 0.000.Keywords: Price, Product Quality, Product Design and Purchasing Decision